2014
DOI: 10.1007/s12275-014-4114-0
|View full text |Cite
|
Sign up to set email alerts
|

The history of aerobic ammonia oxidizers: from the first discoveries to today

Abstract: Nitrification, the oxidation of ammonia to nitrite and nitrate, has long been considered a central biological process in the global nitrogen cycle, with its first description dated 133 years ago. Until 2005, bacteria were considered the only organisms capable of nitrification. However, the recent discovery of a chemoautotrophic ammonia-oxidizing archaeon, Nitrosopumilus maritimus, changed our concept of the range of organisms involved in nitrification, highlighting the importance of ammonia-oxidizing archaea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 124 publications
0
36
1
Order By: Relevance
“…2, 3). The reason for this delay in nitrification may be due to the presence of a small nitrifying community in a soil with low natural pH (3.6 in the A horizon) and low NH 4 + concentrations, although the importance of these factors in understanding bacterial vs. archaeal contributions to nitrification in acidic soils is an area of current research (Prosser and Nicol, 2012; Monteiro et al, 2014). Nevertheless, the hydrolysis of urea to NH 4 + results in the transformation of an N source that is neutral and leachable to an N source that is positively charged and therefore less easily moved through the soil.…”
Section: Resultsmentioning
confidence: 99%
“…2, 3). The reason for this delay in nitrification may be due to the presence of a small nitrifying community in a soil with low natural pH (3.6 in the A horizon) and low NH 4 + concentrations, although the importance of these factors in understanding bacterial vs. archaeal contributions to nitrification in acidic soils is an area of current research (Prosser and Nicol, 2012; Monteiro et al, 2014). Nevertheless, the hydrolysis of urea to NH 4 + results in the transformation of an N source that is neutral and leachable to an N source that is positively charged and therefore less easily moved through the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicated that environmental drivers like substrate (i.e., NH 4 + ) concentration, pH, oxygen availability, salinity, among others, might be responsible for differentiating AOA and AOB abundance and distribution (Martens-Habbena and Stahl, 2011; Hatzenpichler, 2012; He et al, 2012; Prosser and Nicol, 2012; Zhalnina et al, 2012; Zhang et al, 2012). Despite previous attempts to evaluate drivers of natural AOA and AOB population dynamics, there remain large gaps in our understanding of factors that control AOA vs. AOB prominence in numerous ecosystems (Hatzenpichler, 2012; Prosser and Nicol, 2012; Monteiro et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Several types of microbial ammonia oxidation processes with different biochemical mechanisms are known to occur: the first is an aerobic oxidation of ammonia by chemolithotrophic ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA), and the second is an anaerobic process by ANAMMOX bacteria. The biochemical mechanisms of ammonia oxidation in the microorganisms have already been elucidated, and their ecological characteristics are also under the active investigation1234.…”
mentioning
confidence: 99%